Vestibular afferent neurons develop normally in the absence of quantal/glutamatergic input - Regalado Núñez, Katherine; Bronson, Daniel; Chang, Ryan; Kalluri, Radha (Frontiers in Neurology, 2024)
IntroductionThe vestibular nerve is comprised of neuron sub-groups with diverse functions related to their intrinsic biophysical properties. This diversity is partly due to differences in the types and numbers of low-voltage-gated potassium channels found in the neurons’ membranes. Expression for some low-voltage gated ion channels like KCNQ4 is upregulated during early post-natal development; suggesting that ion channel composition and neuronal diversity may be shaped by hair cell activity. This idea is consistent with recent work showing that glutamatergic input from hair cells is necessary for the normal diversification auditory neurons.MethodsTo test if biophysical diversity is similarly dependent on glutamatergic input in vestibular neurons, we examined vestibular function and the maturation of the vestibular epithelium and ganglion neurons by immunohistochemistry and patch-clamp electrophysiology in Vglut3-ko mice whose hair cell synapses lack glutamate.ResultsThe knockout mice showed no obvious balance deficits and crossed challenging balance beams with little difficulty. Immunolabeling of the Vglut3-ko vestibular epithelia showed normal development as indicated by an identifiable striolar zone with calyceal terminals labeled by molecular marker calretinin, and normal expression of KCNQ4 by the end of the second post-natal week. We found similar numbers of Type I and Type II hair cells in the knockout and wild-type animals, regardless of epithelial zone. Thus, the presumably quiescent Type II hair cells are not cleared from the epithelium. Patch-clamp recordings showed that biophysical diversity of vestibular ganglion neurons in the Vglut3-ko mice is comparable to that found in wild-type controls, with a similar range firing patterns at both immature and juvenile ages. However, our results suggest a subtle biophysical alteration to the largest ganglion cells (putative somata of central zone afferents); those in the knockout had smaller net conductance and were more excitable than those in the wild type.DiscussionThus, unlike in the auditory nerve, glutamatergic signaling is unnecessary for producing biophysical diversity in vestibular ganglion neurons. And yet, because the input signals from vestibular hair cells are complex and not solely reliant on quantal release of glutamate, whether diversity of vestibular ganglion neurons is simply hardwired or regulated by a more complex set of input signals remains to be determined.